2014
DOI: 10.1038/nature12970
|View full text |Cite
|
Sign up to set email alerts
|

A cascade of DNA-binding proteins for sexual commitment and development in Plasmodium

Abstract: Commitment to and completion of sexual development are essential for malaria parasites (protists of the genus Plasmodium) to be transmitted through mosquitoes1. The molecular mechanism(s) responsible for commitment have been hitherto unknown. Here we show that PBAP2-G, a conserved member of the ApiAP2 family of transcription factors, is essential for the commitment of asexually replicating forms to sexual development in P. berghei, a malaria parasite of rodents. PBAP2-G was identified from mutations in its enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
450
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 399 publications
(496 citation statements)
references
References 43 publications
18
450
2
6
Order By: Relevance
“…These results indicated that the disruption of AP2-G2 did not abrogate sexual commitment or sex determination but did cause marked developmental defects in the gametocytes, together with a marked reduction of sex-specific gene expression. The phenotypes of the AP2-G2(−)820 parasites obtained in the present study and those reported by Sinha et al were largely similar; i.e., only a small proportion of mature gametocytes was observed in the AP2-G2(−)820 parasites (8). However, the present study showed that despite being indistinguishable from trophozoites, gametocytes were present in the AP2-G2(-)820 parasites as in the original parasites.…”
Section: Significancecontrasting
confidence: 55%
See 4 more Smart Citations
“…These results indicated that the disruption of AP2-G2 did not abrogate sexual commitment or sex determination but did cause marked developmental defects in the gametocytes, together with a marked reduction of sex-specific gene expression. The phenotypes of the AP2-G2(−)820 parasites obtained in the present study and those reported by Sinha et al were largely similar; i.e., only a small proportion of mature gametocytes was observed in the AP2-G2(−)820 parasites (8). However, the present study showed that despite being indistinguishable from trophozoites, gametocytes were present in the AP2-G2(-)820 parasites as in the original parasites.…”
Section: Significancecontrasting
confidence: 55%
“…Thus, there is a long intervening period between the completion of sexual commitment and the onset of sexual differentiation as well as between the expression of the two transcription factors that are associated with these events. If AP2-G2 is downstream in a transcriptional cascade initiated with AP2-G as suggested (8), it may be that the expression of AP2-G2 is silenced at a posttranscriptional level during this interval. At present, however, in vivo evidence for the events occurring during this period is still lacking, and further studies are required to elucidate the relationships between these two transcription factors in gametocytogenesis.…”
Section: Bp) (C and D)mentioning
confidence: 99%
See 3 more Smart Citations